Penerapan Model PBL berbasis Outdoor Study dalam Peningkatan Keterampilan Berpikir Kritis & Kemampuan Argumentasi Siswa - Nurhasanah, Nunun; Hindriana, Anna Fitri; Sulistyono, Sulistyono (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2020)
This study aims to determine the effect of the application of the PBL learning model to the improvement of critical thinking skills and the ability to argue students of SMA Negeri 1 Salem class X even semester 2018/2019 on the concept of environmental pollution. The research method used is quasi-experimental. The study was conducted in two meetings. Learning activities are divided into two parts, namely learning activities outside the classroom (outdoor study) during the PBL 1-3 phase and learning in the classroom during the PBL 4-5 phase. The results showed the application of the PBL model based on outdoor study was carried out well there was an increase in the score of students' critical thinking skills at a pretest score of 18.9 to a posttest of 23.69 the ability of student argumentation in the average experimental class is at level 2, meaning that students already have the ability to submit claims or opinions built by students based on their knowledge and students are able to provide reasons or data to support the claim statement. Control class argumentation ability is at level 1 the positive response of students to learning PBL models based on outdoor studies is 89.4% with very strong criteria.